Recruitment, follow-up and survival in an 11-country cohort study of patients at the end of life and their relatives - Maria E. C. Schelin; Christel Hedman; Pilar Barnestein-Fonseca; Martina Egloff; John Ellershaw; Dagny Faksvåg Haugen; Claudia Fischer; Melanie Joshi; Ida J. Korfage; Urška Lunder; Stephen Mason; Judit Simon; et al. (PLoS ONE, 2025)
Background Large, international cohort studies generate high-level evidence, but are resource intense. In end-of-life care such studies are scarce. Hence, planning for future studies in terms of data on screening, recruitment, retention and survival remains a challenge. Objectives The aim was to describe recruitment, follow-up and survival in a multinational study of patients’ and relatives’ expectations, concerns and preferences at the end of life. Methods In this 11-country cohort study with six months follow-up patients, >18 years old, were included on the basis of an adapted “surprise question” to assess patients´ end of life status. Patients were required to be aware of their limited life expectancy. We collected patient questionnaires (baseline and 1 month), and searched medical records for the date of death. One relative per patient was invited to participate. Results 26735 patients were screened for inclusion, 3065 (11%) were found eligible and were invited to participate, 1509 chose to participate, i.e. 6% of those initially screened. A total of 699 patients (49%) participated in the 1-month follow-up, with proportions varying according to survival time, from 20% if the patient died at month 2, to 75% if the patient died at month 6. Survival time was not associated with patient gender or age, but with diagnosis, country of residence and healthcare setting. Conclusion Approximately 20 times the desired cohort size had to be screened for eligibility. Prognostication was difficult, we noted a wide distribution of survival after inclusion. Patients’ ability to complete follow-up questionnaires declined well before death.